Cu-catalyzed asymmetric regiodivergent electrosynthesis and its application in the enantioselective total synthesis of (-)-fumimycin - Tian Xie; Jianming Huang; Juan Li; Lingzi Peng; Jin Song; Chang Guo (Nature Communications, 2023)
Abstract Quaternary amino acids are one of the essential building blocks and precursors of medicinally important compounds. Various synthetic strategies towards their synthesis have been reported. On the other hand, developing core-structure-oriented cross-dehydrogenative coupling (CDC) reactions, is a largely unsolved problem. Herein, we describe a copper-catalyzed regiodivergent electrochemical CDC reaction of Schiff bases and commercially available hydroquinones to obtain three classes of chiral quaternary amino acid derivatives for the efficient assembly of complex scaffolds with excellent stereocontrol. The electrochemical anodic oxidation process with slow releasing of quinones serves as an internal syringe pump and provides high levels of reaction efficiency and enantiomeric control. The utility of this strategy is highlighted through the synthetic utility in the asymmetric total synthesis of (-)-fumimycin.